EMANCIPATION THROUGH NURSING WITHIN THE CONTEXT OF HEALTH DISPARITIES - Rainier C. Moreno-Lacalle; Rozzano C Locsin (Belitung Raya Foundation, Indonesia, 2019)
Background: Health disparity can be observed using the lens of emancipation through nursing. Objective: This paper aims to describe the concept of emancipation through nursing, situate its position within the theory of ’Emancipation through Nursing,’ and illuminate the implications of caring within the context of health disparity. Methods: The sequential process of Rodgers’ Evolutionary Concept Analysis and Chinn and Kramer’s Process of Theory Construction were applied. Review of the literature utilizing six major databases was conducted using the keywords ‘emancipation’ or ‘empowerment’ and ‘health disparity’ and ‘nursing’ and with year restrictions from 2000-2017. Results: Findings revealed that the attributes of the concept of ‘emancipation through nursing’ are conscientization or critical consciousness, correct and adequate health information, co-construction of a creative process for health service, and collective action. These attributes were preceded by the following antecedents: marginalization, hegemony, the oppressed and the emancipator, centering, and liberation. The resulting features of enlightenment, enervation, empowerment, and evolvement served as constructs that collectively structured the theory of Emancipation through Nursing in the Context of Health Disparities. Conclusion: Nurses worldwide will benefit from descriptions and illuminations of the concepts of emancipation and nursing within the theory of Emancipation through Nursing in the Context of Health Disparities.